Behavioral effects induced by antitumor cleronade diterpenes from Casearia sylvestris and in silica interactions with neuron receptors - Ferreira de Araujo, Everton Jose; Cardoso de Almeida, Antonia Amanda; Silva, Oskar Almeida; Fernandes da Costa, Iwyson Henrique; Rezende-Junior, Luis Mario; Alves Lima, Francisco das Chagas; Cavalheiro, Alberto Jose [UNESP]; Pessoa, Claudia; Moraes, Manoel Odorico de; Pinheiro Ferreira, Paulo Michel (Elsevier B.V., 2017)
Ethnopharmacological relevance: Casearia sylvestris is a medicinal plant traditionally used to treat snakebites, wounds, inflammation and gastric ulcers and scientific supports for have demonstrated its antitumor, antihyperlipidemic and antiparasitic properties. Aim of the study: To assess the effects of a fraction with casearins (FC) on adult mice using classical experimental models of animal behavior and theoretical calculations to verify the interaction of Casearin X (Cas X) with neuron receptors. Materials and methods: Animals divided in 6 groups (n=9/group) were intraperitoneally treated with vehicle (DMSO 4%), FC (2.5, 5, 10 and 25 mg/kg/day) and diazepam (2 mg/kg) for 7 days. Thirty minutes after the last dose of treatment, acute toxicity and behavioral experiments were performed. Results: The highest dose of FC (25 mg/kg/day) caused diarrhea, weight loss and death of one animal. Elevated plus maze test showed that lower doses [2.5 mg/kg/day (36.4 +/- 5.1 s) and 5 mg/kg/day (43.9 +/- 6.2 s)] increased the time spent in open arms (TSOA). Open field test revealed reduction in the number of crossings (54.9%, 51.1%, 48% and 67.7% for 2.5, 5, 10 and 25 mg/kg/day, respectively) in all doses of FC studied and decrease of rearings at 25 mg/kg/day (p < 0.05). Computational calculations showed that the inhibition constant (Ki) for the Cas X -D-1 complex is up to 1000 -fold more favourable than the Cas X-GABA(A) complex. All Delta G degrees values obtained for Cas X -D-1 complexes were more negative than those seen with Cas X-GABA(A) complexes. Conclusions: Findings indicate a probable anxiolytic action of the FC since it reduces the number of crossings and rearings and prolonged the time spent in open arms, without sedative and myorelaxant effects, probably due to the interaction of Cas X with dopaminergic system.
Keywords: Casearins; Physiological parameters; Anxiolytic action; Acute toxicity